Study of the health and socio-economic status of toddy tappers in the Jaffna District. - Sivayagan, S (My University, 1989)
This study inquires into the health status of 730 toddy tappers in two areas (Kokuvil and Mallakam) in the Jaffna district, in the context of their socio- economic background and suggestes methods for improvement in the srtandard of their health.In the absence of an organised occupational health service for these workers,it is suggested that the proposed primary health care centres incorporate this service,including counselling on accident prevention,family planning,alcoholism etc.Research studies in the fields of egronomy are also suggested.